Transformation of various multicenter bondings within bicapped-square antiprismatic motifs: Z-rearrangement - Bakardjiev, Mario; Holub, Josef; Růžičková, Zdeňka; Růžička, Aleš; Fanfrlík, Jindřich; Štíbr, Bohumil; McKee, Michael L; Hnyk, Drahomír (Dalton transactions (Cambridge, England, 2021)
Reported herein are mutual rearrangements in the whole series of seven bicapped-square antiprismatic closo-C2B8H10 by means of high-quality computations that disprove the earlier postulated dsd (diamond-square-diamond) scheme for these isomerizations. The experimentally existing closo-1,2-C2B8H10 was able to be converted to 1,6-, and 1,10-isomers by pyrolysis, and the dsd (diamond-square-diamond) mechanism was offered as an explanation of these processes. However, these computations disprove the postulated dsd scheme for these isomerizations that take place in the ten-vertex closo series. Experimentally observed thermal rearrangements, both in the parent and substituted closo-1,2-C2B8H10, closo-1-CB9H10-, and closo-B10H102-, indirectly support these refined computations. All these processes are based on the new concept of the so-called Z-mechanism, being consistent with a transition state of a boat shape with an open hexagonal belt that results from the initial breakage of three bonds. Such bond breakings and the consequent bond formations bring to mind the shape of the letter Z. In effect, the pattern of multicenter bonding shifts from reactant through a transition state to product. The molecular rearrangements that are available experimentally favour either the axial or equatorial isomers, and this ratio depends on temperature and the type of cluster and its substitution.